2018
DOI: 10.3390/app8091613
|View full text |Cite
|
Sign up to set email alerts
|

An Ant-Lion Optimizer-Trained Artificial Neural Network System for Chaotic Electroencephalogram (EEG) Prediction

Abstract: The prediction of future events based on available time series measurements is a relevant research area specifically for healthcare, such as prognostics and assessments of intervention applications. A measure of brain dynamics, electroencephalogram time series, are routinely analyzed to obtain information about current, as well as future, mental states, and to detect and diagnose diseases or environmental factors. Due to their chaotic nature, electroencephalogram time series require specialized techniques for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 110 publications
0
25
0
1
Order By: Relevance
“…A so-called function "roulette wheel selection (RWS)" is applied for this purpose. Further details of the ALO and the mathematical optimization process are detailed in other studies, such as [48][49][50].…”
Section: Ant Lion Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A so-called function "roulette wheel selection (RWS)" is applied for this purpose. Further details of the ALO and the mathematical optimization process are detailed in other studies, such as [48][49][50].…”
Section: Ant Lion Optimizationmentioning
confidence: 99%
“…The SHO was similarly The applicability of the applied algorithms has been previously demonstrated for other optimization aims. In research by Kose [49] and Francis and Meganathan [60], for example, the ALO was used to improve the performance of the ANN and ANFIS, respectively. The SHO was similarly used by Li et al [61] to train a feed-forward neural network for a heart-related classification problem.…”
Section: Quality Assessment Of Predictive Modelsmentioning
confidence: 99%
“…Finally, in the third stage, the output is predicted according to weights between the output units and hidden units. One of the most important actions and advantages of an ANN is the discovery of nonlinear, statistical data, complex relationships between input and output parameters, and its use in a variety of science and engineering applications, particularly recently [31,[42][43][44][45][46][47]. To achieve this goal, a sufficient number of dataset samples are required to train the ANN with a suitable algorithm.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…A literature review showed that various metaheuristic algorithms have been successfully employed for optimizing the neural computing models, i.e., genetic algorithm [42], particle swarm optimization [43], differential evolution [44], artificial bee colony (ABC) [45], cuckoo search [46], differential flower pollination [47], and ant-lion optimizer [48]. Herein, the weights of the neural computing models were searched and optimized.…”
Section: Introductionmentioning
confidence: 99%